2008
DOI: 10.1103/physrevb.78.125402
|View full text |Cite
|
Sign up to set email alerts
|

Additional levels between Landau bands due to vacancies in graphene: Towards defect engineering

Abstract: We describe the effects of vacancies on the electronic properties of a graphene sheet in the presence of a perpendicular magnetic field: from a single defect to an organized vacancy lattice. An isolated vacancy is the minimal possible inner edge, showing an antidotlike behavior, which results in an extra level between consecutive Landau levels. Two close vacancies may couple to each other, forming a vacancy molecule tuned by the magnetic field. We show that a vacancy lattice introduce an extra band in between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 32 publications
3
36
0
5
Order By: Relevance
“…2 /h steps at higher energies (in contrast with the two 2e 2 /h steps in LL0) are rationalized by the fact that, even for the fully periodic case where random disorder broadening is absent, the two new states within each higher-energy LL are very close in energy [44]. Thus, unrealistically small broadening and a complete absence of disorder would be required to resolve the energy lifting of extended states for LLs different than LL0.…”
Section: B Longitudinal and Transverse Conductivitymentioning
confidence: 99%
See 2 more Smart Citations
“…2 /h steps at higher energies (in contrast with the two 2e 2 /h steps in LL0) are rationalized by the fact that, even for the fully periodic case where random disorder broadening is absent, the two new states within each higher-energy LL are very close in energy [44]. Thus, unrealistically small broadening and a complete absence of disorder would be required to resolve the energy lifting of extended states for LLs different than LL0.…”
Section: B Longitudinal and Transverse Conductivitymentioning
confidence: 99%
“…2), while the conductivity clearly resolves it. The different position of the peaks for SVs and DVs is reminiscent of their behavior when arranged in periodic arrays [44].…”
Section: B Longitudinal and Transverse Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lowest field considered in that reference (beside B = 0 T) was around 300 T, therefore our results can be understood as a low field limit of those presented in Ref. 25.…”
Section: Changing the Magnetic Fieldmentioning
confidence: 64%
“…For example, Ref. 25 showed that vacancy coupling does not depend on their type, however, we showed that these states have a certain symmetry, therefore the coupling strength will also depend on direction, and not only on distance. Divacancies also cause localization, but for fields that we consider, their localization energies are much closer to those of the relativistic LLs, which makes them harder to observe experimentally.…”
Section: Discussionmentioning
confidence: 99%